Primary Care Providers Have Limited Knowledge About STI Screening And HIV PrEP in Men Who have Sex with Men. (4th October 2017) - Walker, Durane; Friderici, Jennifer; Skiest, Daniel
Abstract: Background: Men who have sex with men (MSM) are at greater risk for human immunodeficiency virus (HIV) and other sexually transmitted infections (STIs). Several studies have demonstrated that HIV pre-exposure prophylaxis (PrEP) for MSM can lower rates of HIV acquisition. However, PrEP may lead to risk compensation and higher rates of non-HIV STIs. We hypothesized that PCPs' knowledge of CDC recommendations for STIs and PrEP in MSM would be low. Methods: To assess knowledge of CDC STI screening and PrEP recommendations we emailed an anonymous questionnaire, to 314 primary care physicians and mid-level practitioners employed by Baystate Medical Center, a 716-bed academic medical center in Springfield, MA. Knowledge scores were calculated as the number of correct items, divided by the total number of items. One-way analysis of variance and Fisher's exact test was used to test for knowledge differences between groups. P < 0.05 was considered statistically significant. Results: One hundred and thirty of 314 invited clinicians opted in and 109 completed the survey (35% effective response rate). Most respondents (89%, n = 97) were physicians, the remainder ( n = 12, 11%) were mid-level practitioners. Thirty-seven respondents (34%) reported having been trained in MSM-specific care. The mean ± SD knowledge score was 49% ± 29% (range: 0% to 100%). Knowledge was low whether respondents reported receiving previous training in MSM-specific care or not (knowledge score 49% if yes vs. 48% if no, P = 0.87) or receiving specific STD screening education (knowledge score = 51% if yes vs. 41% if no, P = 0.14). Seventy-two respondents (66%) reported providing care for MSM patients of which 29 (40%) reported having discussed PrEP with at least a few patients in the last year. Among the 29 who discussed PrEP at least once, 13 (45%) correctly answered the PrEP indication question compared with 8 (24%) of those who did not discuss PrEP. Conclusion: PCP knowledge of STI screening guidelines and PrEP indications for MSM is low, even among those PCPs who reported receiving MSM-specific training. In light of studies demonstrating PrEP can lead to lower HIV transmission rates among MSM while potentially increasing STI rates, efforts to educate clinicians on PrEP and STI screening should be a priority. Disclosures: All authors: No reported disclosures.